Activation Strategies for Earth-Abundant Metal Catalysis - Peng, Jingying; Thomas, Stephen P. (Synlett, 2020)
The use of earth-abundant metal-catalysed organic transformations has increased significantly in recent years. Where low-oxidation-state catalysts are required, the in situ activation of metal(II/III) salts offers an operationally simple method to access these catalysts. Here we present the development of activation strategies from the use of reducing organometallic reagents to endogenous activation. Applications in alkene and alkyne hydrofunctionalisation reactions will be used to highlight the synthetic applications of the activation methods discussed.1 Introduction2 In situ Activation Using Organometallic Reagents3 In situ Activation Using Nonorganometallic Reagents4 ‘Activator-Free’ Systems5 Conclusions
Keywords: alkene hydrofunctionalisation; low oxidation state; activation; earth-abundant metal catalysis